A model for multidisciplinary graduate education in modelling and simulation. (26th May 2009) - Mielke, Roland R.; Scerbo, Mark W.; Gaubatz, Kurt Taylor; Watson, Ginger S.
Modelling and Simulation (M&S) is increasingly important in numerous disciplines. M&S also has gained acceptance as a discipline in its own right. There is growing demand for at least two different approaches to M&S graduate education, one path for users and another for developers of M&S. Thus, the traditional department-focused approach is no longer adequate for M&S education. This paper outlines the development of a multidisciplinary approach to M&S graduate education at Old Dominion University. The approach encourages development of a number of M&S programmes, coordinated by university-level oversight, in which all academic colleges participate.